Mesenchymal Stem/Stromal Cells in Skeletal Muscle Are Pro-Angiogenic, and the Effect Is Potentiated by Erythropoietin - Yoshitaka Iso; Sayaka Usui; Hiroshi Suzuki (MDPI AG, 2023)
The aim of this study was to investigate the angiogenic potential of skeletal muscle mesenchymal stem/stromal cells (mMSCs). Platelet-derived growth factor receptor (PDGFR)-α positive mMSCs secreted vascular endothelial growth factor (VEGF) and hepatocyte growth factor when cultured in an ELISA assay. The mMSC-medium significantly induced endothelial tube formation in an in vitro angiogenesis assay. The mMSC implantation promoted capillary growth in rat limb ischemia models. Upon identifying the erythropoietin receptor (Epo-R) in the mMSCs, we examined how Epo affected the cells. Epo stimulation enhanced the phosphorylation of Akt and STAT3 in the mMSCs and significantly promoted cellular proliferation. Next, Epo was directly administered into the rats' ischemic hindlimb muscles. PDGFR-α positive mMSCs in the interstitial area of muscles expressed VEGF and proliferating cell markers. The proliferating cell index was significantly higher in the ischemic limbs of Epo-treated rats than in untreated controls. Investigations by laser Doppler perfusion imaging and immunohistochemistry demonstrated significantly improved perfusion recovery and capillary growth in the Epo-treated groups versus the control groups. Taken together, the results of this study demonstrated that mMSCs possessed a pro-angiogenic property, were activated by Epo, and potentially contributed to capillary growth in skeletal muscle after ischemic injury.